Acute-phase protein behavior in dairy cattle herd naturally infected with Trypanosoma vivax - Sampaio, Paulo Henrique [UNESP]; Fidelis Junior, Otavio Luiz [UNESP]; Marques, Luiz Carlos [UNESP]; Machado, Rosangela Zacarias [UNESP]; Barnabé, Patrícia de Athayde; André, Marcos Rogério [UNESP]; Balbuena, Tiago Santana [UNESP]; Cadioli, Fabiano Antonio [UNESP] (Elsevier B. V., 2015)
Trypanosoma vivax is a hemoprotozoon that causes disease in cattle and is difficult to diagnose. The host-parasite relationship in cattle that are infected by T. vivax has only been poorly studied. In the present study, a total of 429 serum proteinograms were produced from naturally infected animals (NIF) and were compared with 50 samples from control animals (C). The total protein, IgA band, complement C3 β chain band, albumin band, antitrypsin band, IgG band, haptoglobin band, complement C3c α chain band and protein HP-20 band presented higher levels in the serum proteinograms of the NIF group. Inter-alpha-trypsin inhibitor heavy chain H4, α2-macroglobulin, complement C6, ceruloplasmin, transferrin band and apolipoprotein A1 band presented lower levels in this group. There was no significant difference (p<0.05) in acid glycoprotein serum concentration between the NIF and C groups. Acute phase proteins may be useful for understanding the host-parasite relationship, since the antitrypsin band was only present in the NIF group. This can be used as an indicator for infection in cattle that are naturally infected by T. vivax.
Keywords: Bovine; Host-parasite relationship; Tandem mass spectrometry; Trypanosomiasis